Pet rats as a source of hantavirus in England and Wales, 2013. - Lisa Jameson; Surabhi Taori; Barry Atkinson; P.L. Levick; Carol Featherstone; Guda van der Burgt; Noel McCarthy; J Hart; Jane Osborne; Amanda L. Walsh; Tim Brooks; Roger Hewson (2013)
We report the detection of a strain of Seoul hantavirus (SEOV) in pet rats in England and Wales. The discovery followed an investigation of a case of haemorrhagic fever with renal syndrome in Wales. Hantavirus RNA was detected via real-time reverse transcription-polymerase chain reaction (RT-PCR) and classic RT-PCR in pet rats belonging to the patient. Sequencing and phylogenetic analysis confirmed the virus to be a SEOV that is similar, but not identical, to a previously reported United Kingdom strain from wild rats.